NEW METHODOLOGIES IN TEACHING ENGLISH LANGUAGE IN MODERN LIFE (Conference Zone, 2022)
This article talks about the most effective methods of teaching English to students, the most important task of the educational process, Pedagogical (educational) technology, design and interactive teaching methods. given information.